Properties of Electron Beam Hardened Layers made by Different Beam Deflection - Matlák, Jiří; Dlouhý, Ivo (Manufacturing Technology Journal, 2018)
The usage of the high-energy electron beam source enables repeated surface quenching of chosen areas of an engineering part surface. Different techniques of electron beam deflection allow creating of hardened layers of different shapes and thicknesses. Experiments were carried out with 42CrMo4 (1.7225) steel. The deflection modes tested were one-point, 6-point, 11-point, line, field and meander. The influence of process speed and defocusing of the electron beam was also taken into account. The electron beam surface quenching resulted in a very fine martensitic microstructure with a hardness of over 700 HV0.5. The thickness of the hardened layers depends on the deflection mode and is affected directly (except field deflection) by process speed. The maximum hardened depth (NCHD) was 1.49 mm. Electron beam defocusing affects the width of the hardened track and can cause extension of the trace up to 40%. The hardness values continuously decrease from the surface to the material core.
Keywords: Electron beam; surface hardening; 42CrMo4 steel; beam deflection